Phytoplankton distribution in the inner Kara Sea: A comparison of three summer investigations. - Nöthig, Eva-Maria; Okolodkov, Yuri; Larionov, Viktor V; Makarevich, Pavel R (PANGAEA, 2012)
Phytoplankton biomass distribution (chlorophyll a, chl. a) and species composition (cell numbers) were investigated during three expeditions to the Kara Sea with "Akademik Boris Petrov" (BP) in 1997, 1999, and 2000. The distribution of biomass in the estuaries of Ob and Yenisei showed a similar range in 1997 (0.2 to 3.2 µg/l) and 2000 (0.4 to 3.5 ug/l); higher chl. a concentrations during these two years were found in Yenisei than in Ob. In 1999, phytoplankton biomass in the Ob and Ob Estuary was much higher than in 1997 and 2000, with maximum values above 10.0 ug chl. a/l. In 1999, biomass in Yenisei was lower (1.5 to ~5 ug/l) than in Ob but slightly higher than in 1997 and in 2000. During the expedition in 2000, the research area extended farther to the north, here, lowest phytoplankton biomass during all three years was found. Typical summer values for integrated chl.a biomass (surface to bottom) ranged between 6 and 20 mg m**-2. Strong differences existed in species composition in both rivers, the estuaries, and the open Kara Sea. In general, three or four different populations could be distinguished in surface waters: (1) freshwater diatoms together with bluegreen algae in both rivers, (2) centric and small pennate diatoms mainly brackish species in the estuaries, (3) north of 74°N, brackish/marine species dominated, i.e. in 1999 Thalassiosira cfpunctigera and Chaetoceros spp prevailed in the phytoplankton bloom in Ob. (4) At the northernmost, almost marine stations, a region with a more heterogeneous composition of unicellular plankton was encountered. We assume, we found different seasonal signals of phytoplankton development during 1997/2000 and 1999, respectively. However, the yearly fluctuation of freshwater runoff of both rivers seems to have the strongest influence on the timing and duration of phytoplankton blooms, species compositions and biomass standing stocks during summer.
Table 3: Comparison of freshwater species in Ob and Yenisei during the 1997 cruise
Keywords: Akademik Boris Petrov; Area/locality; BP97; BP97-10; BP97-12; BP97-17; BP97-30; BP97-32; BP97-48; BP97-55; BP97-58; DIVERSE; Kara Sea; KaraSea97; MULT; Sampling gear, diverse; Siberian River Run-Off; SIRRO; Species